If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(5x + 12) = 0 Reorder the terms: (-9 + x)(5x + 12) = 0 Reorder the terms: (-9 + x)(12 + 5x) = 0 Multiply (-9 + x) * (12 + 5x) (-9(12 + 5x) + x(12 + 5x)) = 0 ((12 * -9 + 5x * -9) + x(12 + 5x)) = 0 ((-108 + -45x) + x(12 + 5x)) = 0 (-108 + -45x + (12 * x + 5x * x)) = 0 (-108 + -45x + (12x + 5x2)) = 0 Combine like terms: -45x + 12x = -33x (-108 + -33x + 5x2) = 0 Solving -108 + -33x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (-12 + -5x)(9 + -1x) = 0Subproblem 1
Set the factor '(-12 + -5x)' equal to zero and attempt to solve: Simplifying -12 + -5x = 0 Solving -12 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -5x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -5x = 0 + 12 -5x = 0 + 12 Combine like terms: 0 + 12 = 12 -5x = 12 Divide each side by '-5'. x = -2.4 Simplifying x = -2.4Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {-2.4, 9}
| 121=r^2 | | 625=r^2 | | 324=r^2 | | 2x+5=3+5x | | 6-5=4x+1 | | 6x+5=4x+1 | | 5805.86=3.14r^2 | | 4j-9j+3=-3 | | (x-7)(y-5)= | | (5x)=(3x+28) | | (3x-1)(3-8x)= | | y=4(7x+100) | | y=1/2+5(0,3) | | (8k-9)(3k-7)= | | 36^1/2 | | x-49=57 | | 9x+6x-12=-7x+2x-12+5 | | -21=y/4 | | 9x-6=3x+6 | | -b=19 | | 6-3x=-5x-2 | | 2x-3x=3-x | | a-16/18=8/9 | | 1/6(5x-9)=7 | | 7-x=6+14 | | 8-4=x+1 | | 6x+4x=10 | | y=x^2*ln(x+2) | | 15x+3y=39 | | 1200=0.18*x | | 1200=0.18x | | -3/4+3/2-2 |